Acardiac Acephalus Twin diagnosed at delivery: A case report - Jha, Rani (Janaki Medical College Journal of Medical Science, 2016)
Abnormal placental vascular anastomoses in monochorionic twins can give rise to a rare congenital anomaly known as Acardiac twin. With the advancement of antenatal care and ultrasonography many such cases are diagnosed early. However, in underdeveloped country like Nepal where early antenatal care coverage rate is low such cases may be diagnosed late. I report one such case of Acardiac acepahalus twin diagnosed during delivery. Janaki Medical College Journal of Medical Sciences (2015) Vol. 3 (2): 62-65